The Meaning of Word of Mouth and Consumer Considerations in Choosing Institut Andi Sapada - Irwan, Ade; Rosdiana, Rosdiana (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to gain an in-depth understanding of how word of mouth and consumer behaviour shape prospective students’ decisions to choose the Institut Ilmu Sosial dan Bisnis Andi Sapada as their place of study. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and document analysis involving prospective students, current students, and alumni selected using purposive sampling. Data were analyzed interactively through the stages of data reduction, data display, and conclusion drawing, while ensuring data trustworthiness through source and technique triangulation. The findings reveal that word of mouth originating from alumni, current students, families, and other social networks functions as a crucial bridge between the institution’s formal information and the actual experiences of users of educational services, thereby shaping prospective students’ perceptions of the campus reputation, quality, and atmosphere. Furthermore, the consumer behaviour patterns of prospective students are characterized by a combination of rational considerations, such as reputation, program relevance, career prospects, and costs, and emotional considerations, including a sense of comfort, value congruence, and support from families and reference groups in the decision-making process. These findings underscore the importance of managing student experiences and strengthening relationships with alumni as strategic efforts to enhance the attractiveness and trustworthiness of Institut Andi Sapada.